Pathogenetic mechanisms of ascending aortic aneurysm of varied aetiology - O. B. Irtyuga; N. D. Gavrilyuk; I. V. Voronkina; V. E. Uspenskyi; A. B. Malashicheva; O. M. Moiseeva (Российский кардиологический журнал, 2013)
Aim. To assess the impact of disturbed extracellural matrix protein balance and matrix metalloproteinase (MMP) activity on the development of ascending aortic aneurysm (AAA) of varied aetiology. Material and methods. The study included 38 patients with AAA and 17 controls without any aortic pathology. In intra-surgery biopsy samples, the levels and activity of MMP-2, MMP-9, fibrillin, elastin, and collagen were measured. Results. Elevated levels of latent MMP-9 and MMP-2 forms were observed in patients with atherosclerosis and tricuspid aortic valve, compared to controls. In participants with bicuspid aortic valve, the levels of both latent and active MMP-9 forms were higher than in controls. In biopsy samples, the elastin-to-collagen ratio values were elevated in patients with atherosclerosis (1:1,7) and bicuspid aortic valve (1:1,6). Conclusion. The difference in the MMP levels and activity and the increased collagen-to-elastin ratio could be related to the underlying mechanisms of the AAA development in patients with bi- and tricuspid aortic valve.